Estudando as dificuldades de interação em software para gerenciamento de campos de petróleo - Alan T. Ramos, Pedro; Cesar dos Reis, Julio; Jose´ Schiozer, Denis; Alberto de Souza dos Santos, Antonio (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2018)
The decision-making process behind the exploitation of petroleum fields requires deciding the best strategies considering the large investments at stake. Software used to simulate and manage petroleum reservoirs, such as MERO, requires an interactive environment to deal with the massive data and numerous parameters that surround the simulations. However, due to the nature of scientific software development, usability was not taken as a specific goal for MERO. In this investigation, we have carried out an user-centered approach to identify usability issues regarding MERO’s interface. We conducted semi-structured interviews with users and analyzed the content of emails sent by users to the support team. This research identified that despite the massive data, most of the issues that users have to deal with the software are related to error messages and inadequate documentation.